Supply Chain Management in the Sphere of Household Economies in the Modern Economy of Russia - Lilia MirgaziyanovnaYusupova; Irina Arkadevna Kodolova; Tatyana Viktorovna Nikonova; Madina Irekovna Agliullina (International Journal of Supply Chain Management, 2019)
Abstract- Despite the fact that the terms